The impact of Formula 1 event towards PETRONAS stock prices / Jazzilah Jilis - Jilis, Jazzilah (2016)
PETRONAS sponsorship program towards the well-known motorcar racing Formula One event has been long being held by this company. The event of this sponsorship not only involves in local rally team, but also in regional and international arena. Lots of researcher related to event studies interested to know the impact of winning or losing the racing car competition towards the stock return but there were little amount of researchers that studies the investors’ behavior in responding to the event of Formula One. Besides that, many of the researchers studies the effect of stock return or shareholders’ welfare to the sponsoring firms but in terms of the effect of stock prices to one particular company only that sponsor the event has not been performed yet. Therefore, the main objective of this paper is to see what happens to the stock price of PETRONAS Company before and after Formula 1 event relating with the price earnings and availability of news. As such, this study relates the Formula 1 event in Malaysia in year 2014 by using Time Series Analysis where it will be in the form of daily basis and the data were collected from Bursa Malaysia by observing the PETRONAS’ annual report. As for the News Availability, the dummy variable will be applied in order to measure the news. Overall, the results of the study shows that only Price Earnings after the event have a significant relationship towards the closing price while others does not give any evidence of relationship.